2012
DOI: 10.1590/s0103-50532012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Short-term toxicity test: monitoring Klebsiella oxytoca bacterium respiration using a flow injection analysis/conductometric system

Abstract: Neste estudo, foi desenvolvido um teste de toxicidade rápido, utilizando-se a bactéria Klebsiella oxytoca como organismo-teste. Ensaios com Escherichia coli foram usados como referência. A inibição do crescimento bacteriano foi avaliada por um sistema de análise por injeção em fluxo (FIA) com detecção condutométrica do CO 2 produzido durante o processo respiratório. Os resultados foram expressos em termos de CE 50 (concentração efetiva). A bactéria K. oxytoca foi mais resistente que a E. coli. A ordem de sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…These results agree with those of previous studies performed with chlorhexidine compounds that also showed higher sensitivity of D. magna when compared to bacteria and fish (Table 3). Chlorhexidine digluconate toxicity to V. fischeri is similar to the toxicity to Klebsiella oxytoca (EC50 of 1,550 lg/l) but lower than the toxicity to Escherichia coli (EC50 of 320 lg/l) (Guimarães et al 2012). ChD was highly toxic to the algae P. subcapitata, with values as low as 31.1 lg/l causing a 20 % reduction in algae growth rate (i.e.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results agree with those of previous studies performed with chlorhexidine compounds that also showed higher sensitivity of D. magna when compared to bacteria and fish (Table 3). Chlorhexidine digluconate toxicity to V. fischeri is similar to the toxicity to Klebsiella oxytoca (EC50 of 1,550 lg/l) but lower than the toxicity to Escherichia coli (EC50 of 320 lg/l) (Guimarães et al 2012). ChD was highly toxic to the algae P. subcapitata, with values as low as 31.1 lg/l causing a 20 % reduction in algae growth rate (i.e.…”
Section: Discussionmentioning
confidence: 90%
“…ChD was reported to be toxic to bacteria (Guimarães et al 2012). Moreover, two studies reported bioaccumulation of ChD on river microbial biofilms and a significant effect of ChD on the structure of microorganism communities (increase in the proportion of archaea, bacteria and cyanobacteria when compared to algae) at doses of 10 lg/1 (Lawrence et al 2008;Dynes et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Acute toxicity determinations were carried out by measuring the respiration inhibition in Escherichia coli cultures, by using FIAconductometric methodology which was composed of a peristaltic pump, the samples and standards injector, a diffusion cell, a conductivity cell, reagent delivery tubes, ion exchange resins, a conductivity meter, a recorder, and a water bath. 21 The sterilized culture media for E.coli was composed of K 2 HPO 4 (7.0 g), KH 2 PO 4 (3.0 g), sodium citrate (0.5 g), ammonium sulphate (1.0 g), magnesium sulphate (0.2 g) and glucose (20 g) (nal volume: 1 L with deionized water; pH: 7.2). The culture medium was inoculated with the bacteria and le in an oven at 37 C until the bacterial suspension became cloudy.…”
Section: Toxicity Measurementsmentioning
confidence: 99%
“…where C is the nal minus initial CO 2 concentration in the control culture and T is the nal minus initial CO 2 concentration in the test cultures. 21…”
Section: Toxicity Measurementsmentioning
confidence: 99%
“…Various detection techniques have been proposed for FIA methods, including electrochemical methods such as potentiometry, [ 5 ] amperometry [ 6 ] and conductometry, [ 7 ] and spectrophotometric, [ 8 ] fluorometric, [ 9 ] and chemiluminescence (CL) methods. [ 10,11 ]…”
Section: Introductionmentioning
confidence: 99%